Poland’s influence on the European Neighborhood Policy in 2002-2009 - Kołodziejczyk, Lidia (Boundaries and Spheres of Influence in Domestic Politics and International Relations, 2023)
The aim of the text is to present Poland's influence on the European Neighborhood Policy in 2002-2009, when Poland submitted two initiatives concerning this issue. Polish diplomacy also actively participated in discussions on other Neighborhood Policy projects presented and on the direction that the European Union should take in its implementation. At the same time, Poland favored the area of Eastern Europe, which has been one of the main areas of interest of Polish foreign policy for centuries. Its stabilization shapes the Polish national interest not only because of its close proximity, but also because of the imperial policy of the Russian Federation, which is invariably perceived in Poland as the main threat. The analysis of the collected materials showed that the initiatives proposed by the Polish diplomacy were implemented by the European Union, which in the period 2002-2009 led the European Neighborhood Policy to Eastern Europe.